The Correlation between Family Environment and Social Sciences Learning Outcomes during the COVID-19 Pandemic - Dewi, Sintya Pramitha (International Journal of Elementary Education, 2021)
This research was conducted basis on many factors that can affect learning success and have an impact on student learning outcomes. This research aims to determine the significant correlation between family environment with social sciences learning outcomes during the COVID-19 pandemic. The research design of this study is ex-post facto research. The population in this study was 57 students and the number of samples was the same as the population, 57 students. Data collection methods in this study used non-test methods, that are questionnaire for the independent variable of the family environment and document recording for the dependent variable social sciences learning outcomes, the data were analysed using simple regression analysis. Based on the results of the analysis with a significance level of 5%, it was found that there was a significant correlation between the family environment and social sciences learning outcomes during the COVID-19 pandemic with rxy = 0,398 and a large contribution of 15,8%. Based on these results it can be concluded that the family environment can affect student learning outcomes especially social sciences subjects.